Synthesis of bilayer films from regenerated cellulose nanofibers and poly(globalide) for skin tissue engineering applications. (15th January 2021) - Amaral, Heliane R.; Wilson, James A.; do Amaral, Ronaldo J.F.C.; Pasçu, Irina; de Oliveira, Fernando C.S.; Kearney, Cathal J.; Freitas, Jair C.C.; Heise, Andreas
Graphical abstract: Highlights: Amphiphilic bilayer films were synthesized via layer by layer deposition. Regenerated cellulose nanofibers and poly(globalide) were used to produce the films. rCNFs were obtained from an agricultural waste (shells of babassu coconut). No chemical modification steps were required to achieve good adhesion between the layers. The rCNF/PGl bilayer film was successfully employed as a scaffold for skin regeneration. Abstract: Commercial cell-based skin regenerative products are highly expensive, carry the risk of rejection and require a long cell culture period to manufacture. This work describes the synthesis of bilayer films from poly(globalide) (PGl) and regenerated cellulose nanofibers (rCNFs) and their use as a cell-free scaffold to support keratinocyte attachment and proliferation. The method is simple, eco-friendly (as the cellulose precursor is obtained from agricultural waste) and of low cost. The rCNFs were produced by acid hydrolysis and PGl was obtained via enzymatic ring-opening polymerization. The bilayer films were synthesized by layer-by-layer casting at ambient temperature. All the films showed a well-defined interface between PGl and cellulose. The produced rCNF/PGl bilayer films showed cell metabolic activity far superior in comparison with pristine PGl regarding the keratinocyte growth, which illustrates the potential use of these materials in skin tissue engineering.